"She could possibly be a Muslim": hiring of immigrants in Icelandic companies - Loftsdóttir, Kristín; Sigurðardóttir, Margrét Sigrún; Kristinsson, Kári (Stjórnsýslustofnun, 2016)
International research has shown that immigrants are often at a disadvantage in the labor market and their expertise often underappreciated. The objective of this article is to review the recruitment process of companies in services, in regard to attitudes to foreign applicants by human resource managers. The research is based on the “thinking aloud” method, where interviewees in qualitative interviews were asked to think aloud while reviewing applicant information. The researchers fabricated six CVs for female applicants from six countries. After examination and discussion of the CVs, the human resource managers were asked further questions on the recruitment of immigrants in their company. The main findings are that human resource managers seem aware of prejudice against people from Eastern Europe, and were willing to hire a woman from Lithuania or Poland for the job. The findings further indicate that in the Icelandic labor market, prejudice centers strongly around religion, then Islam. The participants did, however, attempt to separate themselves from prejudice against Islam by referring to gender equality. The research further suggests that it might not be relevant to make a sharp distinction between skilled and unskilled workers. The findings suggest that the applicant ?s experience makes a difference when the experience has been gained in Iceland, while being much less important if gained somewhere else. Erlendar rannsóknir benda á að innflytjendur standa oft höllum fæti á vinnumarkaði og sérfræðiþekking þeirra er oft ekki metin að verðleikum. Markmið þessarar greinar er að skoða ráðningarferlið hjá þjónustufyrirtækjum út frá viðhorfum mannauðsstjóra til erlendra umsækjenda. Rannsóknin, sem er eigindleg, byggir á svokallaðri, hugsa upphátt (e. think aloud) aðferð. Rannsakendur útbjuggu sex ferilskrár kvenkyns umsækjenda, frá jafnmörgum löndum, með umsókn um starf bókara hjá stóru þjónustufyrirtæki. Mannauðsstjórar voru beðnir um að lesa yfir starfslýsingu og hugsa svo upphátt á meðan þeir fóru yfir ...